2020
DOI: 10.17485/ijst/v13i29.369
|View full text |Cite
|
Sign up to set email alerts
|

The increasing of Interleukin 6 and Superoxide Dismutase 3 nasal wash in textile industry workers exposed by occupational air pollutant

Abstract: Background: Occupational air pollution exposure in textiles industry which irritates the respiration system triggers the disturbance of the nasal mucosa. IL-6 is produced by monocytes and macrophages as a response for tissue damage. SOD-3 is extracellular enzymes protected the tissue from free radical and chronic inflammation. Objectives: To know if the occupational air pollution affects the increasing of IL-6 and SOD-3 level on nasal wash. Methods: this study used an analytical observational design with cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…vi The previous research showed an inconsistent effect on nasal mucociliary transport-time exposure by wood-dust, outdoor inhalation of gas/fuel station workers and iron-dust, 3,5,6 however, it was strong evidence that occupational air pollutants surrounding the indoor dyeing sector of the textile industry increased Il-6 and SOD3. 4 It was suggested that inflammation and stress oxidative effect might also change the nasal-cilia function and prolonged the nasal mucociliary transport time.…”
Section: Introductionmentioning
confidence: 99%
“…vi The previous research showed an inconsistent effect on nasal mucociliary transport-time exposure by wood-dust, outdoor inhalation of gas/fuel station workers and iron-dust, 3,5,6 however, it was strong evidence that occupational air pollutants surrounding the indoor dyeing sector of the textile industry increased Il-6 and SOD3. 4 It was suggested that inflammation and stress oxidative effect might also change the nasal-cilia function and prolonged the nasal mucociliary transport time.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies also show that NE herbal masks work actively in suppressing high free ROS and result in decreased superoxide dismutase 3 SOD3, leading to an oxidant-antioxidant imbalance. (5) An experimental study showed that the NE herbal mask is better in increasing IgA and improving the pulmonary function in textile workers compared to the regular mask. (6) The ethanol extract of Hibiscus rosasinensis (HRS) contains flavonoids, saponins and steroids and might be responsible for significant inhibition of inflammation, which may involve inhibition of prostaglandins, (7) as well as blocking of the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%